Recent Developments in Cambridge College Libraries - Wilson, Alison (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Cambridge University has three tiers of libraries available to students: the University Library, departmental (subject) libraries and college libraries. Over the past thirty years there has been increasing pressure on the colleges to provide more books, reader places and technical resources in their libraries, with the result that a number of new library buildings, of very different styles, have been opened. Other colleges have opted for refurbishment and extension of existing libraries. These libraries are small (30-100,000 books) and intimate, often open 24 hours a day and with generous provision for lending books. Great importance is placed on keeping them at the heart of the college. Challenges for architects are the sensitive sites, restrictions on changes to listed buildings, and the limited space available. The constricted sites cause difficulties for the builders too. I will consider some solutions to these problems with reference to projects in four colleges: Pembroke, Peterhouse, Corpus Christi and Newnham. At Pembroke architects Freeland Rees Roberts have built an extension to a listed building and at Peterhouse they have adapted an adjoining room. Corpus Christi is moving its library to a Victorian building which has been internally redesigned by Wright + Wright. Newnham demolished a 1960s extension in order to develop the plot more efficiently to a design by John Miller + Partners. All the architects have shown sensitivity to the needs of their clients and ingenuity in making intensive use of limited space.